To analyze Oliver's work using the Zero Product Property for the equation \((x + 3)(x + 4) = 0\):
- According to the Zero Product Property, if the product of two factors equals zero, then at least one of the factors must equal zero.
- This means we should set each factor to zero separately:
- \(x + 3 = 0\) → \(x = -3\)
- \(x + 4 = 0\) → \(x = -4\)
Now, looking at the work recorded in the table:
- The first row \(x - 3 = 0\) is incorrect since that does not correspond to any of the factors from the equation.
- The second row \(x + 4 = 0\) is correct but was expected to have \(x + 3 = 0\) in the first row instead.
Based on this evaluation, the correct assessment is:
No, x − 3 = 0 in the second row should be x + 3 = 0.
Therefore, the correct response to the question is:
No, x − 3 = 0 in the second row should be x + 3 = 0.